AGILITY AND DIGITAL CAPABILITIES AS DRIVERS OF COMPETITIVE ADVANTAGE: A CASE STUDY OF THAI SMES DISTILLERIES - Phatsanat Tarnuphatpong; Aree Naipinit (PEOPLE: International Journal of Social Sciences, 2026)
This investigation explores the structural linkages between agile frameworks, digital readiness, and the achievement of sustained competitive advantage among Thai SME-sized spirits producers. As traditional industries adapt to the digital era, the ability to respond quickly to change and integrate digital tools has become essential for sustained competitiveness. The investigation centers on three primary internal determinants: digital literacy, digital transformation, and organizational agility. Utilizing a structured survey, empirical data were gathered from 190 SME distilleries across Thailand and subsequently analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that organizational agility serves as the most potent direct driver of competitive advantage, with digital transformation also yielding a positive impact. While digital literacy is a crucial precursor to digital transformation, its influence on competitive advantage—both direct and indirect—did not reach statistical significance. These conclusions imply that digital competencies are inadequate on their own; they must be leveraged via agile frameworks to bolster strategic responsiveness. This study extends existing research on SME competitiveness by highlighting the importance of combining digital readiness and organizational agility for achieving success, particularly in highly regulated industries such as alcohol production. It also provides practical insights for SME leaders and policymakers.